Pigmentation and not only sex and age of individuals affects despotism in the Andean condor. - Nancy V Marinero; Verónica B Cailly-Arnulphi; Sergio A Lambertucci; Carlos E Borghi (PLoS ONE, 2018)
Attributes such as sex, age and pigmentation of individuals could correspond to the competitive skills they use to access resources and, consequently, determine their social status when a hierarchy of dominance is established. We analysed patterns of social dominance in relation to sex, age and, for the first time, according to face pigmentation in a large scavenger bird species, the Andean condor (Vultur gryphus). This species displays extreme sexual dimorphism, with males being up to 50% heavier than females. Associated to this, strong hierarchical relationships characterize foraging, roosting and breeding. We recorded agonistic interactions within condor groups while foraging through video recordings in experimental stations. We corroborated a strong despotism by the adult males to the rest of the categories. More interestingly we found this despotism was also expressed by most pigmented birds; juvenile females being completely subordinated and, at the same time, not expressing pigmentation. Importantly, when condors of equal sex and age category fought, the more pigmented individuals were successful. Our results highlight that pigmentation, besides sex and age, is an attribute that also corresponds with social status in the Andean condor, making its hierarchical system more complex.